Uji Aktivitas Antioksidan Ekstrak dan Fraksi n-Heksan, Etil asetat, dan Air Kulit Jambu Biji Australia (Psidium guajava L.) Dengan Metode DPPH (1,1-Difenil-2-Pikrilhidrazil) - Ning Rusmiyati; Desy Ayu Irma Permatasari; Isna Nur Khasanah (Pusat Riset dan Inovasi Nasional, 2023)
Free radicals work by binding to molecules or cells in the body and are very dangerous because they can damage cells in the body and trigger disease. Antioxidants are compounds that can counteract the effects of free radicals. This study aims to determine the antioxidant activity of ethanol extract and the n-hexane, ethyl-acetate and water fractions of Australian guava peel (Psidium guajava L.). Extraction was carried out by maceration method using 70% ethanol. The skin of the Australian guava (Psidium guajava L.) contains alkaloids, flavonoids, tannins, triterpenoids and saponins. Fractionation was carried out with solvents based on polarity differences obtained by the n-hexane fraction, ethyl acetate fraction, and air fraction. Antioxidant test by inhibiting DPPH free radicals (1,1-Diphenyl-2-Picrylhydrazyl) on ethanol extract and n-hexane fraction, ethyl acetate fraction and air at several concentrations, namely 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm. The IC50 calculation results obtained for the ethanol extract were 4.406 µg/mL, the n-hexane fraction was 4.131 µg/mL, the ethyl acetate fraction was 3.812 µg/mL and the air fraction was 3.312 µg/mL. The antioxidant activity with the best IC50 value was the fraction air.